A ‘Normal’ Life. Administrative Violence, Critical Trans Politics and the Limits of Law - Fernandez Vergara, Catalina (Critical Proposals in Social Work, 2021)
“Una Vida ‘Normal’. Violencia Administrativa, Políticas Trans Críticas y los Límites del Derecho”, Dean Spade,